1985
DOI: 10.1073/pnas.82.11.3535
|View full text |Cite
|
Sign up to set email alerts
|

Glycolysis and methylaminoisobutyrate uptake in rat-1 cells transfected with ras or myc oncogenes.

Abstract: A high rate of aerobic glycolysis was catalyzed by rat-i cells transfected with a ras oncogene (ras cells); rat-i cells and rat-i cells transtected with myc oncogene (myc cells) showed a low rate of glycolysis that was increased after exposure of the cells to type B transforming growth factor (TGF-P). The uptake of radioactive methylaminoisobutyric acid or L-methionine via system A of amino acid transport also was accelerated after exposure of these cells to TGF-p, with the myc cells being most sensitive and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 15 publications
6
86
0
Order By: Relevance
“…This has been shown for EAT cells used in this study [35]. Racker et al described that transformation of rat cells with the activated ras gene _ but not the myc gene -increases aerobic glycolysis [31], suggesting that activation of some -but not alloncogenes may cause a shift of the metabolism towards glycolysis under aerobic conditions. Glycolysis is increased also after exposure of cells to hypoxic conditions as in the case of HeLa cells.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This has been shown for EAT cells used in this study [35]. Racker et al described that transformation of rat cells with the activated ras gene _ but not the myc gene -increases aerobic glycolysis [31], suggesting that activation of some -but not alloncogenes may cause a shift of the metabolism towards glycolysis under aerobic conditions. Glycolysis is increased also after exposure of cells to hypoxic conditions as in the case of HeLa cells.…”
Section: Discussionsupporting
confidence: 78%
“…3) suggesting that hypoxically growing cells had shifted their energy metabolism towards glycolysis. Oncogen activation has been shown to increase glycolysis and LDH activity in rat cells under aerobic conditions [31,32]. Specific LDH activity was two-fold higher in rus-transformed NIH-3T3 cells than in non-transformed cells (Fig.…”
Section: Modulation Of Proliferation By Q Is Related To the Metabolicmentioning
confidence: 93%
“…2). A number of oncogenes, including fps, src, and ras have been shown to increase glucose transport and to up-regulate glut1 mRNA and protein levels (3)(4)(5). glut1 gene expression and glucose transport are also stimulated in a variety of cells under hypoxic conditions, a response that is mediated by the transcription factor HIF-1.…”
Section: Oncogenic Transformation Of Mammalian Cells Is Associated Wimentioning
confidence: 99%
“…Stable transfection of oncogenic H-ras V12 into Rat-1 immortalized fibroblasts causes increased glucose uptake and lactate production (Racker et al, 1985;Kole et al, 1991). Moreover, recent studies by Ramanathan et al (2005) have demonstrated that the introduction of an oncogenic allele of H-ras into human fibroblasts already immortalized with the telomerase catalytic subunit, SV40 large T antigen (LT) and small T antigen causes: (i) increased glucose uptake and lactate production; (ii) increased ribose-5-phosphate, a glucose-derived anabolic precursor of DNA and RNA; and (iii) increased sensitivity to the glycolytic inhibitors, 2-deoxyglucose and oxamate.…”
Section: Introductionmentioning
confidence: 99%